2015
DOI: 10.1155/2015/138039
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Phytochemistry of Oleo-Gum Resin ofCommiphora wightii(Guggulu)

Abstract: Guggulu is an oleo-gum resin which exudes out as a result of injury from the bark of Commiphora wightii (Arnott) Bhandari [syn.  Commiphora mukul (Hook. Ex Stocks) Engl; Balsamodendron mukul (Hook. Ex Stocks); Family, Burseraceae]. It has been used in the Ayurveda since time immemorial for the treatment of variety of disorders such as inflammation, gout, rheumatism, obesity, and disorders of lipids metabolism. It is a mixture of phytoconstituents like volatile oil which contains terpenoidal constituents such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 39 publications
0
54
0
11
Order By: Relevance
“…The inhibitory effect of guggulsterones E and Z was very similar to the inhibitory effect of clofibrate. This obser-vation has therapeutic value in myocardial infarction and thromboembolism [5,44].…”
Section: Miscellaneous Activitiesmentioning
confidence: 91%
See 3 more Smart Citations
“…The inhibitory effect of guggulsterones E and Z was very similar to the inhibitory effect of clofibrate. This obser-vation has therapeutic value in myocardial infarction and thromboembolism [5,44].…”
Section: Miscellaneous Activitiesmentioning
confidence: 91%
“…It was clearly observed that guggulosomes had more efficacy than ibuprofen and both guggul and ibuprofen had synergistic effect. The study indicating the anti-inflammatory property of guggul [44,45]. Guggulsterones suppress TNF-induced COX-2 promoter activity and protein expression in vitro in a dose-dependent manner [26].…”
Section: Anti-inflammatory and Antiarthritic Activitymentioning
confidence: 91%
See 2 more Smart Citations
“…This pale yellow or brown oleo-gum resin is an exudate from cracks, fissures, or incisions on the bark of Commiphora wightii, Commiphora mukul, Commiphora abyssinica, Commiphora molmol, and Commiphora Burseraceae [61]. It is composed of phenols, ferulic acids, and other nonphenolic aromatic acids that have the potential to scavenge superoxide radicals, thus, making it significant in combating neurodegenerative diseases that have oxidative stress as a substantial implication [62].…”
Section: Guggulumentioning
confidence: 99%